Hubungan antara Asupan Gizi dengan Kadar Hemoglobin Ibu Hamil - Anggit Kartikasari; Tia Srimulyawati; Indri Siti Maryam (Jurnal Kebidanan Harapan Ibu Pekalongan, 2020)
Nutritional intake during pregnancy has an effect on fulfilling iron needs because there is an increase in the mass expansion of red blood cells, the need for iron increases and this will have an impact on anemia. The incidence of anemia in pregnant women is still quite high, based on Riskesdas (2013) states that 37.1% of pregnant women have anemia due to malnutrition. The purpose of this study was to determine the relationship between nutritional intake and hemoglobin levels of pregnant women in the UPTD Ciawigebang District Health Center. This research method is quantitative, sampling with a total sampling technique with a total of 25 pregnant women. The instrument used was the observation sheet and the analysis used the Spearman Rank. Based on the results of the univariate analysis study, most pregnant women had moderate nutritional intake, namely around 68% (17 people), while most pregnant women had Hb levels <11gr% or mild anemia, namely around 56% (14 people). The results of the bivariate analysis showed a value (r = 0.411 p = 0.041), this indicated that there was a significant relationship between nutritional intake and hemoglobin levels of pregnant women. It was concluded that there was a significant relationship between nutritional intake and hemoglobin levels of pregnant women. It is expected for pregnant women to pay more attention to nutritional intake in each so that the fulfillment of mother and fetus nutrition is fulfille